2011
DOI: 10.1098/rspb.2010.2598
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental dispersal by a microendemic burrowing reptile (Dibamidae)

Abstract: Intercontinental dispersal via land bridge connections has been important in the biogeographic history of many Holarctic plant and animal groups. Likewise, some groups appear to have accomplished trans-oceanic dispersal via rafting. Dibamid lizards are a clade of poorly known fossorial, essentially limbless species traditionally split into two geographically disjunct genera: Dibamus comprises approximately 20 Southeast Asian species, many of which have very limited geographical distributions, and the monotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…Migration via 593 Beringia has been inferred to be the most probable route giving rise 594 to this disjunction for organisms of various ages (e.g. Wang et al, 595 2004;Townsend et al, 2011;Vila et al, 2011;Li and Wen, 2013; Nemeobiinae and Euselasiinae (Fig. 2), but the major diversifica-610 tion in all subfamilies started around 50-55 Mya in the early Table 1 Parameters from biogeographical model testing in BioGeoBEARS.…”
Section: Styx Infernalismentioning
confidence: 98%
“…Migration via 593 Beringia has been inferred to be the most probable route giving rise 594 to this disjunction for organisms of various ages (e.g. Wang et al, 595 2004;Townsend et al, 2011;Vila et al, 2011;Li and Wen, 2013; Nemeobiinae and Euselasiinae (Fig. 2), but the major diversifica-610 tion in all subfamilies started around 50-55 Mya in the early Table 1 Parameters from biogeographical model testing in BioGeoBEARS.…”
Section: Styx Infernalismentioning
confidence: 98%
“…The possibility of chydorid taxa being widely distributed in an everwet tropical forest floor, in swamps and wetlands stretching out across Eurasia and North America during the Eocene in a continuous warm climatic belt, with relatives in Central America and the Asian tropics, until cooling pushed the taxa further southwards and caused extinction in North America and the Palaearctic, should at least be considered. As Christenhusz and Chase (2013) Townsend et al (2011) suggested the same age for the SE Asian-Mexican disjunction in dibamid lizards using molecular methods and noted the importance of the boreotropical forest belt for the dispersal of their group. We suggest that the biome has played a crucial role in aquatic invertebrate dispersal during the Eocene as well.…”
Section: African Extinction or Boreotropics?mentioning
confidence: 99%
“…The oldest tapiromorph perissodactyl fossils dated to the lower Eocene (Missiaen and Gingerich, 2012). In the reptiles, the legless lizard family Dibamida has two genera with its centre of diversity in SE Asia (Dibamus Duméril et Bibron, 1839) and a monotypic disjunct genus (Anelytropsis Cope, 1885) in Mexico, the result of a Cenozoic (Eocene) dispersal event (Townsend et al, 2011). Several trans-Pacific (not Amphi-Pacific) disjunctions in animals that include New Zealand and oceanic islands in the Pacific, have received a lot of attention.…”
Section: Amphi-and Trans-pacific Disjunctions In Terrestrial Biotamentioning
confidence: 99%
See 1 more Smart Citation
“…The charismatic Fijian and Tongan iguanas (Brachylophus [16]) are postulated to have colonized Melanesia by transoceanic rafting from the Neotropics, but neither the mechanism nor the timing of the colonization is well understood. Similarly, the fossorial lizard family Dibamidae is represented by 22 species in southeast Asia and a single species that is endemic to Mexico, likely the result of transoceanic or overland dispersal across Beringia in the Eocene [17].…”
Section: Introductionmentioning
confidence: 99%